Pengenalan Gross Motor Skills pada Siswa Sekolah Dasar untuk Meningkatkan Keterampilan Gerak Dasar - Fajar, Muhammad Maulana; M. Irfan; M. Alif Hamzah (Program Studi Pendidikan Jasmani, Universitas Samudra, 2025)
Gross Motor Skills (Fundamental Movements) form the foundational competencies that students must develop before progressing to advanced motor skills in various sports disciplines. Students with strong fundamental movement skills have a greater potential to acquire specialized sports skills, and they are more likely to achieve higher levels of physical fitness. Given the critical role of these foundational movements, an introductory program was conducted at MIS Nurul Siti Aisyah Ishak Deli Tua. The method employed in this program involved a modified Snakes and Ladders game, specifically designed to enhance the fundamental movement abilities of elementary students. Each numbered square on the game board incorporated basic movement commands to reinforce essential motor patterns. The program involved 30 students, organized into 5 groups, under the guidance of lecturers participating in community service initiatives. The activities were implemented in three main stages: planning, execution, and supervision. Continuous monitoring and evaluation were carried out in collaboration with the principal and teaching staff at MIS Nurul Siti Aisyah Ishak, ensuring the ongoing development of students' foundational motor skills throughout their educational journey. The participants demonstrated high levels of enthusiasm and engagement throughout the program, indicating a positive response to the modified Snakes and Ladders approach in improving fundamental movement skills. It is anticipated that this initiative will significantly contribute to enhancing the foundational physical competencies of students at MIS Nurul Siti Aisyah Ishak Deli Tua.